British traders in the East Indies, 1770-1820 : 'at home in the Eastern seas' - Miller, W. G. (Woodbridge : The Boydell Press, 2020)
An in-depth study of the British traders who extended British commercial activity beyond the area controlled by the East India Company.
Title from publisher's bibliographic system (viewed on 21 Sep 2020).
Keywords: Great Britain -- Commerce -- East Indies; East Indies -- Commerce -- Great Britain; Great Britain -- Commerce -- History -- 18th century; Great Britain -- Commerce -- History -- 198th century